Science and Technology on the Internet PLUS by Gail Clement - Flora G. Shrode (Issues in Science and Technology Librarianship, 1996)
This article reviews the book Science and Technology on the Internet PLUS. (Internet Workshop Series Number 4) Berkeley, CA: Library Solutions Press, 1995, by Gail Clement.